CCAFS site atlas – Usambara / Lushoto - Sijmons, Koert; Kiplimo, Joyce; Förch, Wiebke; Thornton, Philip K.; Radeny, Maren A.O.; Kinyangi, James (2013)
CCAFS site atlas for Usambara / Lushoto, Tanzania.